Redirected entanglements in the digital supply chain. - Hockenberry, Matthew (Cultural Studies)
The supply chain is not just a metaphor for the production of the modern world, it is the very means through which that world is made material. Through the careful coordination of bodies and materials, it delivers the glut of goods necessary for daily life – even as it ties that life to human rights abuses, violent regimes of extraction, and environmental devastation at unprecedented scales. But while software has long been part of every supply chain, the supply chain is, itself, part of every bit of software. Developers speak of digital production in the language of logistics. They write about algorithms as frequently as distribution networks, worry about just-in-time production as much as engineering, and decorate their tools with illustrations copied from shipping companies or factories. The design of data is thought of the same way as the objects that will access it. This article interrogates the emergence of the supply chain, and the logistical modes of operation it entails, as metaphor for managing the digital distribution of data – adapting approaches from the critical study of logistics in order to re-incorporate the political, social, and environmental attachments that 'digital supply chains' attempt to obfuscate. To this end, it considers discourses around power and cultural politics that mirror critiques of traditional logistical infrastructures. Instead of conflict minerals, for example, conflict domains; in place of security concerns around cargo containers, data containers; rather than workers on the factory floor, labourers in a digital network of 'sweatshops.' These comparisons reveal differences between traditional supply chains and their digital counterparts – the most troubling of which is their infrastructural instability. With components that can be replaced while retaining their essential shape, those who depend on digital platforms can find themselves open to all sorts of redirected entanglements.